Analysis of computational complexity in holographic lens-less projection - Kowalczyk, Adam; Bieda, Marcin; Makowski, Michał; Ducin, Izabela; Kakarenko, Karol; Suszek, Jarosław; Sobczyk, Artur (Photonics Letters of Poland, 2014)
In lens-less projection the illuminating wavefront must be modified, so that after propagation on a certain distance it would form an image on the screen. Formed images will be displayed with frame rate minimum 20 fps in case of animated movie. Thus, the speed of computing is extremely important. Computing might be performed by central processing unit (CPU) or graphics processing unit (GPU). Reaching a compromise between computational complexity (as well as the time of computing) and quality of obtained image is needed. This leads to a need to a proper iteration number of the algorithm, its parameters and size of computing matrices. Full Text: PDF References S. W. Keckler, W. J. Dally, B. Khailany, M. Garland and D. Glasco, "GPUs and the future of parallel computing", IEEE Micro, 31(5), 7-17 (2011). CrossRef T. Shimobaba, T. Ito, N. Masuda, Y. Ichihashi, and N. Takada, "Fast calculation of computer-generated-hologram on AMD HD5000 series GPU and OpenCL", Opt. Express 18, 9955-9960 (2010). CrossRef A. Kowalczyk, M. Bieda, M. Makowski, M. Sypek, and A. Kolodziejczyk, "Fiber-based real-time color digital in-line holography", Appl. Opt. 52, 4743-4748 (2013). CrossRef C.-J. Cheng, W.-J. Hwang, C.-T. Chen, and X.-J. Lai, "Efficient FPGA-Based Fresnel Transform Architecture for Digital Holography", J. Display Technol. 10, 272-281 (2014). CrossRef Y.-H. Seo, H.-J. Choi, J.-S. Yoo, and D.-W. Kim, "An architecture of a high-speed digital hologram generator based on FPGA", Journal of Systems Architecture, Vol. 56. pp. 27-37 (2009). CrossRef M. Makowski, "Minimized speckle noise in lens-less holographic projection by pixel separation," Opt. Express 21, 29205-29216 (2013). CrossRef T. Utsugi and M. Yamaguchi, "Speckle-suppression in hologram calculation using ray-sampling plane," Opt. Express 22, 17193-17206 (2014). CrossRef F. Wyrowski and O. Bryngdahl, "Iterative Fourier-transform algorithm applied to computer holography," J. Opt. Soc. Am. A 5, 1058-1065 (1988). CrossRef M. Makowski, I. Ducin, K. Kakarenko, J. Suszek, M. Sypek, and A. Kolodziejczyk, "Simple holographic projection in color," Opt. Express 20, 25130-25136 (2012). CrossRef